First Thoughts. - Wilby, Peter (New Statesman, 2013)
The article offers news briefs related to Great Britain as of January 11, 2013. Topics include public opinion in the U.S. regarding economic conditions and policy in Great Britain; education policy in Great Britain regarding non-traditional "free schools" for alternative and experimental education; and the death of the former South African cricketer Neil Adcock.